KHILAFAH, IMARAH DAN IMAMAH DALAM KONSTELASI POLITIK ISLAM Analisis Komperatif tentang Wacana Bentuk Negara dan Sistem Pemerintahan - Lendrawati Lendrawati (UIN Imam Bonjol Padang, 2021)
The polemic about the form of state and system of government emerged after the death of Rasulullah Muhammad SAW, because of the two roles by the Prophet Muhammad as both the bearer of both the treatise and the head of state in Medina. On the other hand there is no concrete message from him who will replace it after him. Term Khilafah, Imarah and Imamah become a study that is always uptodate in the realm of Islam politics. The word